(untitled) (Al-Qamar, 2019)
Women Day is celebrated throughout the world on 8th March. On this day women belonging to different parts of the world raise their voice on social media to make people realize women rights. This article reveals the history and background of “Women Day” and the slogan “My body, my will”. Women who want freedom from religious and social limits and restrictions think that they would become more comfortable by gaining this freedom. They want equality in generation, but it is quite illogical. Allah Almighty has made their body totally different from men. Their body symmetry and field of action both are different from men. If they want peace and comfort in their life, they should return to their Creator, Allah Almighty and follow the instruction manual revealed by Him i.e. Quran. Islam is the only religion that provides women their due rights and respect.